Late Bajocian bioevents of ammonoid immigration and colonization in the Arequipa basin (Pumani river area, Ayacucho, southern Peru) - Fernández López, Sixto Rafael (2013)
Strata of the Socosani Formation in the Pucayacu and Pumani sections (Ayacucho Department, Peru), along several kilometers, have yielded Upper Bajocian ammonoid fossil-assemblages characterized by the occurrence of juvenile individuals belonging to endemic or pandemic taxa, such as Megasphaeroceras and Spiroceras respectively. In addition, certain Bajocian taxa relatively common in the Mediterranean-Caucasian Subrealm, but very scarce in the Eastern Pacific Subrealm, such as the strigoceratid Cadomoceras and the phylloceratid Adabofoloceras, occur in this area. These Late Bajocian bioevents of regional appearance of immigrant ammonoids and even sustained colonization should be associated with an episode of maximum deepening, maximum relative sea-level rise and highest oceanic accessibility of a Bajocian-Bathonian deepening/shallowing palaeoenvironmental cycle in the Arequipa Basin, during the Late Bajocian Niortense Biochron.